Interview of Victor Young by Dian O. Belanger - Young, Victor (Byrd Polar Research Center Archival Program, 2009)
The Antarctic Deep Freeze oral history project was funded by a grant from the National Science Foundation and supported by the Antarctic Deep Freeze Association. The original paper copies and unaltered tapes have been deposited in the library of the National Science Foundation. Vic Young joined the Seabee Reserve after admiring their work and attitude in World War II. Back in active duty, he was a Seabee warrant officer when he responded to the call for Antarctic volunteers in 1955. At the Caterpillar Company in Peoria he oversaw the modification of heavy D-8 tractors for use on snow. He was Little America's operations officer-in charge of getting the ships offloaded, the station built, the Byrd Trail reconnaissance party started out. A plane with half the returning trail party crashed off-course, and heading a search and rescue party along the trail, Young saw danger signs in the surface. Later, on a fuel-caching mission, they uncovered crevasses and, as driver Max Kiel was filling one chasm, his tractor fell backwards into another, killing him. Over the winter, he organized the materials for Byrd Station on numbered sleds. In the spring, Deep Freeze II, Army crevasse experts blasted a safe trail through the crevasse zone. Young led the first tractor train to inland Byrd and directed its construction. National Science Foundation Antarctic Deep Freeze Association